MULTICULTURAL CRISIS AND MIGRATION PROBLEM IN EUROPEAN STATES - Rusul, Oleh (Proceedings of the National Aviation University Series Philosophy Cultural, 2022)
Introduction. The article analyzes the socio-cultural environment of European countries in the context of the crisis of multiculturalism and migration processes. Emphasis is placed on defining strategies for overcoming the crisis of multiculturalism in European countries. Emphasis is placed on the need to further search for acceptable models of European multicultural practices. The aim of the studyis to identify the features and ways to solve the current multicultural crisis in Europe. The tasks of the studyare to determine the causes of the multicultural conflicts, the prospects for optimizing intercultural relations, the nature of European migration policyand ways of overcoming the multicultural crisis. Research methodology is a civilizational approach, the principle of objectivity, analysis, and synthesis methods. Research results. The study compares the approaches to the implementation of multicultural policy in Europe and the United States. The specifics and features of the current state of the multicultural space of European states are researched. Prospects for the development of multicultural policy in European countries are determined. The influence of the cultural, economic components and migration aspect in the formation of cultural diversity in the EU is indicated. Discussion. It is indicated that it takes time to sufficiently note the success or failure of the process of resolving the migration crisis and establishing intercultural relations in the context of cultural diversity. Соnclusion. States that the existing cultural diversity in European countries requires effective steps to promote constructive intercultural dialogues, especially on the most pressing issues, namely the interaction of local cultures within foreign cultures. In such a situation, further support for cultural diversity has priority for the sustainable formation of European multiculturalism in future, otherwise socio-cultural conflicts cannot be avoided.